Tetrataenite phase in Antarctic meteorites - Nagata, Takesi; Funaki, Minoru (1987)
P(論文) Four Ni-rich iron meteorites containing tetrataenite (γ'-phase of Fe-Ni metal) and 2 LL chondrites containing the γ'-phase are provisionally selected as the standard γ'-rich meteorites. They are Santa Catharina and Twin City Ni-rich ataxites, taenite lamellae from Toluca and Itutinga octahedrites and St. Severin and Appley Bridge LL chondrites. The contents of γ'-phase in these standard γ'-rich meteorites were determined by the Mossbauer spectral analysis and their magnetic hysteresis and thermomagnetic characteristics were examined. The magnetic criteria for γ'-rich meteorites derived from the present study are summarized as follows : (1) Remanence coercive force (H_<RC>) is anomalously large (i. e. H_<RC>≥500 Oe). (2) The apparent Curie point is 560-580℃. (3) The initial heating thermomagnetic (TM) curve of the γ'-phase is flat below about 500℃ and then sharply drops down to the apparent Curie point. (4) After heating to temperatures above 700℃, the γ'-phase is broken down to the ordinary disordered γ-phase, so that the first-cooling curve and subsequent TM curves have the characteristics of those of γ-phase. (5) Because of the break-down of γ'-phase during the heating procedure, H_C and H_<RC> are much reduced, by up to one order of magnitude or more from their pre-heating initial values. In the present experimental study, 5 Antarctic L chondrites and 4 Antarctic LL chondrites are magnetically examined. The Antarctic chondrites which satisfy the five criteria for γ'-rich meteorites are Yamato-74354 (L6), -74362 (L6), -74442 (L6), ALH-76009 (L6) and Y-790964 (LL). departmental bulletin paper